Ameloblastin attenuates RANKL‐mediated osteoclastogenesis by suppressing activation of nuclear factor of activated T‐cell cytoplasmic 1 (NFATc1). Issue 2 (13th August 2018) - Chaweewannakorn, Wichida; Ariyoshi, Wataru; Okinaga, Toshinori; Fujita, Yuko; Maki, Kenshi; Nishihara, Tatsuji
Abstract : Ameloblastin (Ambn) is an extracellular matrix protein and member of the family of enamel‐related gene products. Like amelogenin, Ambn is mainly associated with tooth development, especially biomineralization of enamel. Previous studies have shown reductions in the skeletal dimensions of Ambn‐deficient mice, suggesting that the protein also has effects on the differentiation of osteoblasts and/or osteoclasts. However, the specific pathways used by Ambn to influence osteoclast differentiation have yet to be identified. In the present study, two cellular models, one based on bone marrow cells and another on RAW264.7 cells, were used to examine the effects of Ambn on receptor activator of nuclear factor kappa‐B ligand (RANKL)‐induced osteoclastogenesis. The results showed that Ambn suppresses osteoclast differentiation, cytoskeletal organization, and osteoclast function by the downregulation of the number of tartrate‐resistant acid phosphatase (TRAP)‐positive multinucleated osteoclasts, actin ring formation, and areas of pit resorption. The expression of the osteoclast‐specific genes TRAP, MMP9, cathepsin K, and osteoclast stimulatory transmembrane protein (OC‐STAMP) was abolished in the presence of Ambn, while that of nuclear factor of activated T cells cytoplasmic 1 (NFATc1), the master regulatory factor of osteoclastogenesis, was also attenuated by the downregulation of c‐Fos expression. In Ambn‐induced RAW264.7 cells, phosphorylation of cAMP‐response element‐binding protein (CREB), c‐Jun N‐terminal kinase (JNK), and p38 mitogen‐activated protein kinase (p38 MAPK), but not extracellular signal‐regulated kinase 1/2 (ERK1/2), was reduced. Calcium oscillation was also decreased in the presence of Ambn, suggesting its involvement in both RANKL‐induced osteoclastogenesis and costimulatory signaling. B‐lymphocyte‐induced maturation protein‐1 (Blimp1), a transcriptional repressor of negative regulators of osteoclastogenesis, was also downregulated by Ambn, resulting in the elevated expression of v‐maf musculoaponeurotic fibrosarcoma oncogene family, protein B (MafB), B‐cell lymphoma 6 (Bcl6), and interferon regulatory factor‐8 (Irf8). Taken together, these findings suggest that Ambn suppresses RANKL‐induced osteoclastogenesis by modulating the NFATc1 axis. Abstract : Ameloblastin (Ambn) suppresses receptor activator of nuclear factor kappa‐B ligand (RANKL)‐induced osteoclastogenesis in three specific pathways; inhibition of JNK and p38 mitogen‐activated protein kinase (MAPK)‐mediated c‐Fos activation, calcium oscillation and cAMP‐response element‐binding protein (CREB)‐mediated nuclear factor of activated T cells cytoplasmic 1 (NFATc1) upregulation, and B‐lymphocyte‐induced maturation protein‐1 (Blimp1)‐mediated negative regulation of osteoclastogenesis